THE IMPACT OF PROFITABILITY ON STOCK RETURNS: A COMPARATIVE ANALYSIS BETWEEN COMPANIES WITH HIGH AND LOW LEVERAGE LEVELS - Lento, George; Dananjaya, Yanuar (Faculty of Economics and Business Universitas Pelita Harapan, 2024)
Various research has shown a positive relation between profitability and stock return. Higher profitability increases company value, and thus drives stock prices higher. We found that the relation is much weaker in companies with high leverage compared to companies with low leverage. The reason might be that in highly leveraged companies, the cash flow resulting from profit is mainly used to serve debt obligation, leaving little left for the stockholder. The result is important for stock investors to avoid putting too much emphasis on company profitability in making investing decisions.